Effects of Composting Different Types of Organic Fertilizer on the Microbial Community Structure and Antibiotic Resistance Genes - Zeming Zhou (Microorganisms, 2020)
Organic fertilizer is a major carrier that stores and transmits antibiotic resistance genes (ARGs). In the environment, due to the application of organic fertilizers in agriculture, the increasing diversity and abundance of ARGs poses a potential threat to human health and environmental safety. In this paper, the microbial community structure and ARGs in different types of organic fertilizer treated with composting were examined. We found that the abundance and diversity of ARGs in earthworm cast organic fertilizer were the lowest and the highest in chicken manure organic fertilizer. Interestingly, the abundance and diversity of ARGs, especially beta-lactam resistance genes, sulfonamide resistance genes, and macrolide-lincosamide-streptogramin B (MLSB) resistance genes, in organic fertilizers were reduced significantly, while composting caused no significant change in mobile genetic elements (MGEs), where antibiotic deactivation and the use of efflux pumps were the two most dominant mechanisms. It was clear that removal of ARGs became more efficient with increasing reduction in the bacterial abundances and diversity of potential ARG hosts, and integron-mediated horizontal gene transfers (HGTs) played an important role in the proliferation of most ARG types. Therefore, the reduction in ARGs was mainly driven by changes in bacterial community composition caused by composting. Furthermore, rather than HGTs, the diversity and abundance of bacterial communities affected by compost physical and chemical properties were the main drivers shaping and altering the abundance and diversity of ARGs, which was indicated by a correlation analysis of these properties, antibiotic residues, microbial community structure, and ARGs. In general, high-temperature composting effectively removed antibiotic residues and ARGs from these organic fertilizers; however, it cannot prevent the proliferation of MGEs. The insights gained from these results may be of assistance in the safe and rational use of organic fertilizers by indicating the changes in microbial community structure and ARGs in different types of organic fertilizer treated with composting.